Medical weight management protects against weight gain during the COVID‐19 pandemic - Sarah R. Barenbaum; Katherine H. Saunders; Karina M. Chan; William J. Crowley; Ilana P. Redmond; Anthony J. Casper; Katie C. Hootman; Rajasekhar Ramakrishnan; Louis J. Aronne; Alpana P. Shukla (Obesity Science & Practice, 2022)
Abstract Background American adults have gained weight during the COVID‐19 pandemic. Little is known about how patients who are medically managed for overweight and obesity, including patients who are prescribed antiobesity pharmacotherapy, have fared. Objective To assess the COVID‐19 pandemic's effect on weight, food choices, and health behaviors in patients receiving medical treatment for overweight or obesity. Methods Adult patients treated at an urban academic weight management center between 1 May 2019 and 1 May 2020 were electronically surveyed between 23 February and 23 March 2021. The survey assessed changes in weight, eating, behaviors, and the use of antiobesity medications (AOMs) following issuance of social distancing/stay‐at‐home policies in March 2020. Results In 970 respondents, median percent weight change for those taking AOMs was −0.459% [interquartile range −5.46%–(+3.73%)] compared to +2.33% [IQR −1.92%–(+6.52%)] for those not taking AOMs (p < 0.001). More participants achieved ≥5% weight loss if they were taking AOMs compared to those who were not (26.7% vs. 15.8%, p = 0.004), and weight gain ≥5% was also lower in those taking AOMs (19.8% vs. 30.3%, p = 0.004). Patients with pre‐pandemic BMI ≥30 kg/m2 taking AOMs experienced the greatest weight reduction, and there was greater weight loss associated with increased physical activity. Conclusions and Relevance Medical weight management protected against weight gain during this period of the COVID‐19 pandemic. Increased physical activity, decreased alcohol intake, and use of AOMs were factors that contributed to this protective effect.